VERIFYING HYPOTHESIS ON THE CORRELATIVE FUNCTION OF GAUSSIAN PROCESS - Mesropyan, N. H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2004)
The paper presents a criterion of verifying hypothesis on the correlative function observed by stationary Gaussian process with zero average value.
Keywords: Gaussian process; criterion of verifying hypothesis; correlative function